The Importance of Hydration and Nutrient-Dense Foods for Optimal Physical Performance in Athletes - Dita Rosyalita (Mandalika Journal of Medical and Health Studies, 2025)
This article explores the critical role of hydration and nutrient-dense foods in optimizing physical performance among athletes. Utilizing a qualitative research methodology, this study conducts a comprehensive literature review to examine existing evidence on the effects of hydration status and dietary intake on athletic performance. The findings indicate that adequate hydration significantly enhances physical capabilities, including endurance, strength, and recovery. Dehydration is shown to impair performance and increase the risk of injuries. Furthermore, the consumption of nutrient-dense foods, which are rich in vitamins, minerals, and macronutrients, is essential for maintaining energy levels and supporting metabolic functions during training and competition. The study highlights specific food groups, such as fruits, vegetables, whole grains, and lean proteins, that contribute to optimal athletic performance. Additionally, it discusses the importance of individualized nutrition plans tailored to the unique needs of athletes, considering factors such as training intensity, duration, and environmental conditions. Recommendations include implementing hydration strategies and promoting education on the benefits of nutrient-dense foods to enhance athletic performance. This research underscores the necessity of prioritizing hydration and proper nutrition in athletic training regimens to achieve peak performance and overall health.